2022
DOI: 10.3390/life12030455
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Genotoxic Activity of Wastewaters Produced after Water-Steam Distillation of Bulgarian Rosa damascena Mill. and Rosa alba L. Essential Oils

Abstract: The steam distillation of valuable rose essential oil from R. damascena Mill. and R. alba L. generates large volumes of wastewaters. Although such wastewaters are bio-pollutants, they contain valuable bioactive compounds. In this study we investigated the cytotoxic/genotoxic and anti-cytotoxic/anti-genotoxic potential of these products. We used cytogenetic methods for induction of chromosome aberrations and micronuclei in two different experimental test-systems: ahigher plant and human lymphocyte cultures. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Wastewaters from rose oil production are phytocomplexes, rich in water-soluble components, meaning that their biological activities are due to the overall action (complementary or antagonistic) of all their ingredients. What they have in common is that the four wastewaters can serve as important raw materials for producing cytotoxically and genotoxically safe commercial products [49]. The obtained results allow us to view R. gallica and R. as potential antiherpes agents.…”
Section: Discussionmentioning
confidence: 76%
“…Wastewaters from rose oil production are phytocomplexes, rich in water-soluble components, meaning that their biological activities are due to the overall action (complementary or antagonistic) of all their ingredients. What they have in common is that the four wastewaters can serve as important raw materials for producing cytotoxically and genotoxically safe commercial products [49]. The obtained results allow us to view R. gallica and R. as potential antiherpes agents.…”
Section: Discussionmentioning
confidence: 76%
“…The stable anti-E. coli activity may possess a practical significance, due to the proven safety of WWR. In our previous study, we investigated the cytotoxic/genotoxic and anti-cytotoxic/anti-genotoxic potential of these products in different experimental treatment regimens [32]. The results obtained showed that the genotoxic activity of the distillation effluents of R. alba and R. damascena was low.…”
Section: In Vitro Assessment Of Biological Activity Of L Plantarum Ac...mentioning
confidence: 99%
“…Both types of waste products exhibited anti-genotoxic effects against N-methyl-N0-nitro-N-nitrosoguanidine as a direct mutagen, and cytoprotective/genoprotective effects to promote a reduction in DNA damage. As can be seen, these effluents fall into the category of bio-pollutants, but they contain valuable bioactive compounds and exhibit interesting biological properties [32]. We related the exhibited biological activities to the total flavonoid content of the two waste products-tannins in R. damascena were 1.61 ± 0.05 mg/mL, and in R. alba tannins were 2.16 ± 0.35, flavonoids 1.14 ± 0.01 mg/mL and 1.01 ± 0.01 mg/mL, and total polyphenols 7.2 ± 0.2 and 7.6 ± 0.3 mg/mL, respectively [18].…”
Section: In Vitro Assessment Of Biological Activity Of L Plantarum Ac...mentioning
confidence: 99%
“…Bulgaria and Turkey are globally known for the rose oil (Slavov et al, 2021). The tiny wield of the rose oil production lead to massive quantities of by-products (Gateva et al, 2022). Previous researches evaluated the composition of the ethanol extract dried rose (Ro sa Damascena Mill.)…”
Section: Introductionmentioning
confidence: 99%